Effects of high fidelity patient simulators as teaching learning strategies on learning outcomes among nursing diploma students in Malaysia / Fong Ka Ling - Fong, Ka Ling (2018)
Simulation education with High Fidelity Patient Simulators (HFPSs) is a teaching and learning tool that serves as a bridge between classroom learning and real-life clinical experience for novice learners. Optimization desired learning outcomes of nursing students is challenged by lack of experiential learning in multiple disciplinary settings and failures in communication between health care providers exposing patients to adverse events that threaten patient safety. What makes HFPS so useful is its ability to simulate realistic clinical situations and settings with no risk to the safety of patients. This study aimed to examine the effectiveness in the learning outcomes (knowledge, skills performance, critical thinking, learners' satisfaction and self-confidence) using an adult code blue simulated programme on a High Fidelity Patient Simulator (HFPS) and low fidelity patient manikin (LFPM) for nursing students in Malaysia. This is a quasiexperimental pre and post-test study. The universal sampling included all year-3 diploma-nursing students (N=389) from three participating nursing schools in Malaysia. Instruments used were 30-single best questions for knowledge, 40-items skills performance observational checklist, 75-items of California Critical Thinking Disposition Inventory (CCTDI) for critical thinking and 36-items likert scale for satisfaction and self-confidence. All instruments went through back translation from English to Bahasa Malaysia. All instruments were distributed and pre-tested by all students prior a lecture delivered on managing deteriorating patient. Students and assessors were double blinded in the selection of control and intervention groups whether using HFPS or LFPM. Briefing was given to both students and assessors for control and intervention groups for the roles and responsibilities held in skills performance learning outcome using HFPS or LFPM. The same instruments were distributed and post-tested immediately after students' exposed to HFPS or LFPM but the 30-single best questions were given to all students 2 months later. The demographic characteristics of students were 20-year-old 259 (66%), predominantly female, n=359 (92%) and n=30 (8%) male students. Majority of students (n=384, 98%) possess SPM equivalent qualification. Students were majority from average academic performance, CGPA of 3 to 3.5, has n=110 (61.1%) in control and n=112 (53.6%) from the iii intervention groups. Students with previous simulation training was n=155 (40%) while those never been exposed was n=234 (60%). A repeated-measures analysis of variance revealed a statistically significant effect of intervention groups with HFPS as teaching learning strategy after controlling for demographic characteristics: knowledge (p<0.05, η2=0.1460), skill performance (p<0.05, η2=0.744), critical thinking (p<0.05, η2=0.119) and satisfaction and self-confidence (p<0.05, η2=0.636). The critical thinking overall means score was found decreased for both post-test intervention and control groups. However, truth-seeking scores shown increment post-test (intervention, 0.86±SD6.71; control, 0.45±SD6.61) adversely decrements in CCTDI subscales. All demographic characteristics have no association with the learning outcomes and non-significant correlation between the each type of learning outcomes in this study. The utmost value of this study is to create awareness and management of change in the current nursing education system to enhance learning, instill the importance of patient safety practices and achieving the learners' satisfaction and confidence in learning process. However, there are pitfalls in supporting the use of simulation education in practice and the learners' ability to transfer learned outcomes to clinical practice in long-term retention. In conclusion, the intervention groups using HFPS had positive effects in learning outcomes and simulation education promotes new innovative experiential learning that enhancing the quality of nursing profession of this country.